A Note Towards - Kappenberg, Claudia (The International Journal of Screendance, 2019)
Some reflections on the development of screendance since the launch of the International Journal of Screendance almost 10 years ago, taking the long view with regards to the relation between innovation, knowledge, history and teaching.